(untitled) (Web of Teachers: Inderscience Research, 2025)
Green bonds have emerged as a vital financial instrument for promoting sustainable development and addressing environmental challenges. This article explores the investment potential of green bonds, focusing on their role in advancing environmental, social, and governance (ESG) goals while providing attractive investment opportunities. Through an analysis of global trends, market dynamics, and comparative performance with traditional bonds, this study evaluates the benefits, risks, and future prospects of green bonds in the financial market. Additionally, case studies of successful green bond projects illustrate their practical applications and impact. The findings highlight the growing importance of green bonds in sustainable finance and offer insights for investors seeking to align their portfolios with sustainability objectives.